Ping-Pong Energy Transfer in Covalently Linked Porphyrin-MoS2 Architectures - Canton-Vitoria, Ruben; Scharl, Tobias; Stergiou, Anastasios; Cadranel, Alejandro; Arenal, Raul; Guldi, Dirk Michael; Tagmatarchis, Nikos (Angewandte Chemie International Edition, 2020)
Molybdenum disulfide nanosheets covalently modified with porphyrin were prepared and fully characterized. Neither the porphyrin absorption nor its fluorescence was notably affected by covalent linkage to MoS2. The use of transient absorption spectroscopy showed that a complex ping-pong energy-transfer mechanism, namely from the porphyrin to MoS2 and back to the porphyrin, operated. This study reveals the potential of transition-metal dichalcogenides in photosensitization processes.
CRIS-Team WoS Importer:2020-02-07